A bacterial effector counteracts host autophagy by promoting degradation of an autophagy component. (27th May 2022) - Leong, Jia Xuan; Raffeiner, Margot; Spinti, Daniela; Langin, Gautier; Franz‐Wachtel, Mirita; Guzman, Andrew R; Kim, Jung‐Gun; Pandey, Pooja; Minina, Alyona E; Macek, Boris; Hafrén, Anders; Bozkurt, Tolga O; et al.
Abstract: Beyond its role in cellular homeostasis, autophagy plays anti‐ and promicrobial roles in host–microbe interactions, both in animals and plants. One prominent role of antimicrobial autophagy is to degrade intracellular pathogens or microbial molecules, in a process termed xenophagy. Consequently, microbes evolved mechanisms to hijack or modulate autophagy to escape elimination. Although well‐described in animals, the extent to which xenophagy contributes to plant–bacteria interactions remains unknown. Here, we provide evidence that Xanthomonas campestris pv. vesicatoria (Xcv) suppresses host autophagy by utilizing type‐III effector XopL. XopL interacts with and degrades the autophagy component SH3P2 via its E3 ligase activity to promote infection. Intriguingly, XopL is targeted for degradation by defense‐related selective autophagy mediated by NBR1/Joka2, revealing a complex antagonistic interplay between XopL and the host autophagy machinery. Our results implicate plant antimicrobial autophagy in the depletion of a bacterial virulence factor and unravel an unprecedented pathogen strategy to counteract defense‐related autophagy in plant–bacteria interactions. Synopsis: A bacterial effector protein degrades autophagy component SH3P2. This counteracts the host cell's NBR1‐mediated defensive autophagy. Xanthomonas campestis pv. vesicatoria suppresses autophagic turnover in the host cell. Type‐III effector XopL was identified as the cause of this suppression. XopL functions by ubiquitinating host autophagy component SH3P2, which is then degraded in a proteasome‐dependent manner. XopL is itself degraded by NBR1‐mediated selective autophagy. We term this "effectorphagy". Suppression of autophagy counteracts defense‐related selective autophagy in plant‐bacteria interactions. Abstract : Bacterial leaf spot is an important plant disease caused by Xanthomonas infection. This report provides a snapshot of an evolutionary arms race in which bacterial effector proteins simultaneously target and are themselves targeted by the host cell autophagy machinery.